Modern Technologies in Enhancing Infrastructure Sustainability: A Comprehensive Review - Jawad, Zainab Qusay; Ali, Mustafa (Ann Publisher, 2025)
Background. This article analyzes contemporary infrastructure sustainability trends, focusing on using modern technology to enhance building project sustainability. Aim. AI and IoT technologies improve infrastructure management by monitoring systems and predicting maintenance requirements. Smart materials like self-healing concrete and high-performance concrete extend structural life and reduce maintenance costs, boosting project sustainability. Methods. Innovative water management methods like rainwater collecting and wastewater reuse help urban projects save water. Result. Innovative building technology like 3D printing reduces material waste and boosts efficiency. However, switching to renewable energy sources like solar and wind energy reduces environmental effect and non-renewable energy usage. Conclusion. Previous studies show that new technologies like AI and 3D printing lower building costs and enhance environmental efficiency. Implementation. To make cities more climate-resilient, future research should produce smart materials, improve water and energy management, and integrate decentralized energy systems.